ANALISIS PENERAPAN AKUNTANSI PENDIDIKAN DI SMP AMKUR BENGKAYANG - Eni Veronika; Nuraini (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This article is the result of research on the analysis of the application of accounting applied to smp amkur begkayang , the purpose of this study is to determine the suitability of the accounting application carried out by smp amkur Eni Veronika with generally accepted accounting principles. This research uses descriptive analysis method, which is to carefully explain certain phenomena and test hypotheses with theory. As for the results of this study, the author suggests that sekolah in the recording process do not calculate depreciation for fixed assets, madrasas only prepare balance and profit and loss reports, and do not compile cash flow reports and notes on financial statements. Thus, based on the description of the discussion and research results, it can be argued that the application of accounting at smp amkur amal dan kurban Eni Veronka is not in accordance with generally accepted accounting principles.